Two novel species of Aspergillus section Nigri from indoor air - Željko Jurjević; Stephen W. Peterson; Gaetano Stea; Michele Solfrizzo; János Varga; Vit Hubka; Giancarlo Perrone (IMA Fungus)
Aspergillus floridensis and A. trinidadensis spp. nov. are described as novel uniseriate species of Aspergillus section Nigri isolated from air samples. To describe the species we used phenotypes from 7-d Czapek yeast extract agar culture (CYA), creatine agar culture (CREA) and malt extract agar culture (MEA), with support by molecular analysis of the β-tubulin, calmodulin, RNA polymerase II (RPB2), and translation elongation factor-alpha (TEF) gene amplified and sequenced from 56 air isolates and one isolate from almonds belonging to Aspergillus section Nigri. Aspergillus floridensis is closely related to A. aculeatus, and A. trinidadensis is closely related to A. aculeatinus. Aspergillus brunneoviolaceus (syn. A. fijiensis) and A. uvarum are reported for the first time from the USA and from the indoor air environment. The newly described species do not produce ochratoxin A.